Innovation and Practice of Integrated Public Service System for Digitally Enabled Lifelong Learning for All People - Lin, Yufan; Lin, Jianming; Xu, Binli (Global Journal of Educational Studies, 2024)
Lifelong learning for all has gradually become a norm in developing education policies in various countries. Innovation and Practice of Integrated Public Service System for Digitally Enabled Lifelong Learning for All People attempts to analyze and address the issues above from the data continuous development and improvement perspective. These issues include Unequal distribution of resources, Rapid technological upgrading, Lack of appropriate platforms, and An urgent need for personalized learning, Data security and privacy. China has made some progress in promoting the construction of a digitally empowered learning society while facing some challenges and problems. The solutions include: Strengthen the overall planning of the platform. Integration of crucial application scenarios. Implementing data governance to build a lifelong learning data warehouse. Using platforms to strengthen the application of learning outcomes. Construction of platform network security guarantee system.